2013
DOI: 10.4018/jmcmc.2013010106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Web Accessibility on Search Engines and Webometrics Ranking

Abstract: Previous researches have highlighted the importance of web accessibility of a website. Its importance has made the W3C (World Wide Web Consortium) come up with Web Content Accessibility Guidelines (WCAG) as a guideline for developing an accessible website. Amongst websites available in the web wide world, many of them are fall under the education institution website category. These education institution websites are mostly the first door that people will go to visit to get information about education services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The importance and effects of marketing in search engines for universities and educational institutions were confirmed by studies conducted in academic marketing. Ayu and Elgharabawy (2013) investigated the relationship between the accessibility of websites and positioning in the search results of institutions providing higher education [1]. The study conducted by Xu and Gao (2012) confirmed that the performance of the website of universities in placement in search results lags far behind expectations of students [22].…”
Section: Changing Consumer Behaviour Determining Marketing Activitiesmentioning
confidence: 92%
“…The importance and effects of marketing in search engines for universities and educational institutions were confirmed by studies conducted in academic marketing. Ayu and Elgharabawy (2013) investigated the relationship between the accessibility of websites and positioning in the search results of institutions providing higher education [1]. The study conducted by Xu and Gao (2012) confirmed that the performance of the website of universities in placement in search results lags far behind expectations of students [22].…”
Section: Changing Consumer Behaviour Determining Marketing Activitiesmentioning
confidence: 92%
“…To collect necessary data different sources are used such as: search engines (Ayu & Elgharabawy, 2013;Halibas et al, 2020), various scientific and commercial webometric databases.…”
Section: Methodsmentioning
confidence: 99%
“…However none of the aforementioned renowned university ranking systems consider the web presence of the universities as a ranking factor. On the other hand several existing studies have shown the usefulness of ranking the universities based on their web presence (Aguillo et al 2008;Ayu and Elgharabawy 2013;Patel and Parmar 2018;Dastani et al 2019). A Spanish research group known as Cybermetrics Lab 1 initiated the webometrics university ranking.…”
Section: Introductionmentioning
confidence: 99%